TINJAUAN YURIDIS TINDAK PIDANA PENYALAHGUNAAN NARKOTIKA TERHADAP PELAJAR - Putri Hafidati (SUPREMASI HUKUM, 2023)
The phenomenon of the rise of narcotics in society has become common knowledge that narcotics distribution is still continuing its efforts to pressure law enforcement to take the drug problem more seriously. The development of drug abuse must be suppressed in addition to endangering children and adolescents and adults, but also the nation's generation. This is what should be a concern since the enactment of the law on narcotics. In addition to economic factors, the tendency of women to work in the drug industry is social because it shows that they are part of modern society and can overcome the hustle and bustle. The type of narcotic used, the personality of the user, and the situation or condition of the user all play an important role in the effect that drug abuse has on a person. A person's physical, psychological, and social aspects are usually affected by drug addiction. The majority of drug users are teenagers or young people. It is closely related to the intense curiosity of teenagers. Keywords: Abuse; Drugs; Legislation.